NASKAH PUBLIKASI PERAN KEPEMIMPINAN KEPALA SEKOLAH MEMODERASI PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KINERJA GURU (STUDI PADA SMK NEGERI DI KOTA PEKALONGAN) - Sukowati, 12.5202.0172; sunarto, Sunarto (Jurnal Mahasiswa Pasca Sarjana, 2014)
The purpose of this study is to examine and analyze the role of school leadership and competence moderate the influence of motivation on teacher performance studies at SMK in the town of Pekalongan. Research methods with quantitative approaches questionnaire data collection techniques using questionnaires, system surveys, questionnaires, observation, interviews and dokumentasi.Populasi in this study were all teachers SMK bersatatus Pekalongan city and civil servants are already certified in Pekalongan city amounted to 140 teachers. The analysis used in this study is a regression technique (regression) to test the hypothesis t - test at the 5% level of significance (Î± = 0.05). The results showed no effect of motivation on teacher performance, the existence of positive and significant impact on the performance of the competence of teachers, the leadership role of the principal has no effect on teacher performance, the role of school leadership motivation moderate the significant effect on the performance of teachers and the lack of effect of leadership role moderate the principal competency on teacher performance.Keywords: Leadership principals moderate the motivation and competence of the teacher performance